Fenomena Sarkasme Komunikasi: Analisis Gaya Komunikasi Selebgram di Media Sosial - Amelinda, Ria; Jumriani, Jumriani; Andriani, Andriani (LP2M IAIN Palopo, 2023)
This research focuses on sarcasm and the communication style of the celebrity influencer Bunda Corla. The aim of this study is to understand the sarcasm expressed by Bunda Corla on Instagram and the communication style used during live streaming. This research employs a descriptive qualitative research method, which is used to obtain information related to the object under study. Data collection techniques include observation, listening, and documentation. Data is analyzed by collecting, reducing, and drawing conclusions from the data. The results show that the sarcasm frequently expressed by Bunda Corla on the Instagram social media platform includes the words bandit, dog, and bastard. The communication style used by Bunda Corla on Instagram during live broadcasts is categorized into two styles: the controlling style, characterized by the intention or desire to persuade, control, and influence others, and the withdrawal style, characterized by communication that is inappropriate.